Unraveling angioedema: diagnostic challenges and emerging therapies - Johnson, Felix; Hofauer, Benedikt (Frontiers in Immunology, 2025)
Bradykinin-mediated angioedema comprises rare but potentially life-threatening disorders, most notably hereditary angioedema (HAE) due to C1 inhibitor (C1-INH) deficiency or dysfunction. Diagnosis is often difficult, as these conditions can resemble urticaria variants, leading to misdiagnosis and delays in care. Distinguishing features are critical, since bradykinin-mediated forms do not respond to antihistamines or corticosteroids. This review summarizes the differential diagnoses of angioedema, including urticaria variants, cheilitis granulomatosa, and hypocomplementemic urticarial vasculitis, highlighting clinical and diagnostic clues. Particular focus is given to HAE—its subtypes (Type I, Type II, and normal C1-INH), pathophysiology, presentation, and genetic basis. Acquired angioedema and drug-induced forms, such as ACE inhibitor–associated angioedema, are also discussed. The therapeutic landscape is rapidly evolving, spanning acute and prophylactic approaches. Options include C1-INH concentrate, kallikrein inhibitors, bradykinin receptor antagonists, and factor XII inhibitors. While these advances expand treatment opportunities, they also complicate decision-making for patients and physicians. Furthermore, emerging CRISPR-based gene editing therapies represent innovative approaches that pose complex ethical dilemmas, and their long-term safety and efficacy have yet to be established. Although novel therapies reduce attack frequency, their true impact on quality of life is not fully established. Comparative effectiveness data are limited, long-term safety—particularly of gene-based therapies—is unknown, and the real-world utility of new oral on-demand agents for acute therapy is uncertain, especially in severe pharyngeal or laryngeal attacks that may hinder swallowing. Current guidelines remain unclear on the need for short-term prophylaxis in patients already receiving effective long-term prophylactic therapy. In conclusion, despite major therapeutic advances, persistent challenges and unanswered questions underscore the need for pragmatic, patient-centered, long-term studies to optimize care.